A qualitative study on the dietary management experience of patients after bariatric surgery based on the COM-B model - HUA Mingbo, YUAN Haijuan, ZHAO Shuai, WANG Tianxiu, XU Yeming, ZHAO Yuqiu, WEI Xiao, WANG Daorong (Xin yixue)
Objective To explore the real experience of diet management in patients after bariatric and metabolic surgery， so as to provide theoretical basis for formulating postoperative dietary management plans for patients. Methods Based on the capability， opportunity， motivation-behavior （COM-B） model， 15 patients who had undergone bariatric and metabolic surgery and returned for follow-up at the Gastrointestinal Surgery Outpatient Clinic of Northern Jiangsu People’s Hospital from January to May 2024 were selected for semi-structured interviews. The data were analyzed using directed content analysis. Results Based on the interview content， a total of 3 themes and 10 sub-themes were extracted， including the constraints of physical and cognitive abilities on dietary management （early postoperative discomfort symptoms affecting dietary behavior， limited access to dietary management knowledge， overly broad dietary guidance）； the influence of environmental factors on dietary management （the positive role of social and family support， the constraints of social situations on dietary management， the economic burden restricting continuous intervention）； and the impact of internal psychological motivations on dietary management （improper emotional coping leading to loss of control over diet， the challenge of habitual behaviors to dietary management， psychological contradictions and conflicts in dietary management， self-reflection and growth in dietary management）. Conclusions Patients after bariatric metabolism surgery face multiple challenges in dietary management， including physical and psychological constraints from individuals， insufficient social and family support， and emotional distress. Medical staff should assist patients in identifying and addressing obstacles in dietary management， provide individualized dietary guidance， improve the diversified social support system， enhance the sustainability of dietary management， and help patients achieve more ideal weight loss results， thereby improving their quality of life.